Indigenous knowledge and learning in Asia/Pacific and Africa perspectives on development, education, and culture - Kapoor, Dip; Shizha, Edward (Palgrave Macmillan, 2010)
"This collection makes a unique contribution towards the amplification of indigenous knowledge and learning by adopting an inter/trans-disciplinary approach to the subject that considers a variety of spaces of engagement around knowledge in Asia and Africa"--Provided by publisher.